Using Brief Cognitive Restructuring and Cognitive Defusion Techniques to Cope With Negative Thoughts. (May 2016) - Larsson, Andreas; Hooper, Nic; Osborne, Lisa A.; Bennett, Paul; McHugh, Louise
Negative thoughts, experienced by 80% to 99% of the non-clinical population, have been linked to the development of psychopathology. The current study aimed to compare a cognitive restructuring and cognitive defusion technique for coping with a personally relevant negative thought. Over a 5-day period, participants used either a restructuring, defusion, or control strategy to manage a negative thought. Pre- and post-intervention participants reported (a) believability of the thought, (b) discomfort associated with the thought, (c) negativity associated with the thought, and (d) willingness to experience the thought. Daily online questionnaires assessing the total frequency of negative thought intrusions and their level of willingness to experience the negative thought were also used. Also, 10 positive and negative self-statements were rated on the same scales, and self-report measures of mood and psychological flexibility were completed. Findings indicated that defusion lowered believability, increased comfort and willingness to have the target thought, and increased positive affect significantly more than the control and cognitive restructuring. Within groups, cognitive restructuring also made significant gains in target thought discomfort, negativity, and "willingness to have" in the same direction as defusion but the no-instruction control did not. Negative thought frequency was reduced in the defusion group, maintained in the restructuring group, and increased in the no-instruction control group. Similar trends emerged from the secondary outcome measures, that is, the effects of the strategies on the positive and negative self-statements. The current findings support the efficacy of using defusion as a strategy for managing negative thoughts.